A conceptual model of natural land degradation based on regressive pedogenesis in semiarid tropical environments. (22nd May 2018) - Vasu, Duraisamy; Tiwary, Pramod; Chandran, Padikkal; Singh, Surendra Kumar; Ray, Sanjay Kumar; Butte, Pravin; Parhad, Vilas
Abstract: Land degradation occurs in all the climatic regions, however, the adverse effects are more pronounced in the semiarid tropical (SAT) environments due to increasing aridity and water scarcity. Though natural processes can also cause land degradation, it is generally attributed to anthropogenic factors. In this study, we elucidate the role of climate and landscape driven soil forming processes in land degradation through a conceptual model. For this, morphological, physical, and chemical properties of the soils occurring in a part of the SAT Deccan Plateau region, India, were characterized. The trend of climatic variables, namely, the mean annual rainfall, potential evapotranspiration, and maximum summer temperature during the last century (1901–2010) showed that the increase in aridity negatively influenced the soil forming processes. The results showed that rainfall variability, temperature, potential evapotranspiration, and hydrological behaviour of the SAT soils were the primary drivers of the soil forming processes and they were identified through examination of the soil variability by factor analysis. The depth distribution of selected indicators (% clay, pH, calcium carbonate, exchangeable sodium percentage, exchangeable magnesium percentage, and hydraulic conductivity) indicated that the current pedogenic processes operating in the SAT environment caused the undesirable modification in soil properties. Through our conceptual model, we discuss the mechanism of the formation of pedogenic carbonate, subsoil sodicity, and subsequent reduction in hydraulic conductivity which leads to the land and vegetation degradation in the SAT environments.